Fast and Straightforward Method for the Quantification of Pazopanib in Human Plasma Using LC-MS/MS. Issue 2 (April 2018) - Verheijen, Remy B.; Thijssen, Bas; Rosing, Hilde; Schellens, Jan H. M.; Nan, Lianda; Venekamp, Nikkie; Beijnen, Jos H.; Steeghs, Neeltje; Huitema, Alwin D. R.
Abstract : Background: Pazopanib is an angiogenesis inhibitor approved for renal cell carcinoma and soft-tissue sarcoma. Studies indicate that treatment with pazopanib could be optimized by adapting the dose based on measured pazopanib plasma concentrations. Methods: We describe the validation and clinical application of a fast and straightforward method for the quantification of pazopanib in human plasma for the purpose of therapeutic drug monitoring and bioanalytical support of clinical trials. Stable isotopically labeled 13 C, 2 H3 -pazopanib was used as internal standard. Plasma samples were prepared for analysis by protein precipitation using methanol and diluted with 10 mmol/L ammonium hydroxide buffer. Chromatographic separation was performed on a C18 column using isocratic elution with ammonium hydroxide in water and methanol. For detection, a tandem mass spectrometer, equipped with a turbo ion spray interface was used in positive ion mode at m/z 438 → m/z 357 for pazopanib and m/z 442 → m/z 361 for the internal standard. Results: Final runtime was 2.5 minutes. All validated parameters were within pre-established limits and fulfilled the FDA and EMA requirements for bioanalytical method validation. After completion of the validation, the routine application of the method was tested by analyzing clinical study samples that were collected for the purpose of therapeutic drug monitoring. Conclusions: In conclusion, the described method was successfully validated and was found to be robust for routine application to analyze samples from cancer patients treated with pazopanib.